Propagação acústica modal no talude continental das regiões Sul e Sudeste Brasileiras - Valente, Marcia Helena Moreira. (2018)
The study of the acoustic propagation along the Brazilian continental slope is the object of this work. A theoretical model of acoustic propagation was developed from the initial propositions for deep ocean, suggested by Bucker and Munk. More specifically, due to the complex variability of the Brazilian water masses, in some situations the well-established models of Bucker and Munk were not adequate to accurately describe the acoustic propagation in such regions. In order to overcome these difficulties, a new regional average profile was calculated based on the historical data of CTD (Conductivity, Temperature and Density) from southern and southeastern Brazil. Thus, it was possible to adapt the theory to the climatology of the continental slope of the Brazilian South Atlantic. This new model was also tested for a distinct situation, frontal to Arraial do Cabo city. Finally, based on such model and for a frequency band delimited between 100Hz and 1 kHz, we establish in a pioneer way the criteria for which there is a robust equivalence between modal propagation and ray tracing theories. Finally, it is expected that such studies will help in the future planning of campaigns aimed at obtaining and analyzing acoustic tomography in large areas of interest for both economic and defense.